2021
DOI: 10.1145/3448120
|View full text |Cite
|
Sign up to set email alerts
|

One More Bite? Inferring Food Consumption Level of College Students Using Smartphone Sensing and Self-Reports

Abstract: While the characterization of food consumption level has been extensively studied in nutrition and psychology research, advancements in passive smartphone sensing have not been fully utilized to complement mobile food diaries in characterizing food consumption levels. In this study, a new dataset regarding the holistic food consumption behavior of 84 college students in Mexico was collected using a mobile application combining passive smartphone sensing and self-reports. We show that factors such as sociabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 130 publications
2
45
0
Order By: Relevance
“…53 Some of the key challenges in detecting events include wearability and comfort, differentiation between eating and drinking episodes, and mobility confounds (wearability necessitates real-world use which inevitably leads to non-food-related head movements). [56][57][58] Sensor-based approaches can either be employed as a form of semiautomatic data collection 59 (i.e., to log instances of eating that are intended to be annotated using human computation approaches), 60 or retrospectively recorded in more detail (manually) by the patient (e.g., 54,[61][62][63] ); or as fully automatic food intake sensing platforms (i.e., as a complete substitute for manual data entry). Automatic journaling at a coarse level of granularity (e.g., logging instances or durations of eating episodes) is still much more robust and reliable than attempting to infer specific food content and portion size.…”
Section: Sensing Food Practicementioning
confidence: 99%
“…53 Some of the key challenges in detecting events include wearability and comfort, differentiation between eating and drinking episodes, and mobility confounds (wearability necessitates real-world use which inevitably leads to non-food-related head movements). [56][57][58] Sensor-based approaches can either be employed as a form of semiautomatic data collection 59 (i.e., to log instances of eating that are intended to be annotated using human computation approaches), 60 or retrospectively recorded in more detail (manually) by the patient (e.g., 54,[61][62][63] ); or as fully automatic food intake sensing platforms (i.e., as a complete substitute for manual data entry). Automatic journaling at a coarse level of granularity (e.g., logging instances or durations of eating episodes) is still much more robust and reliable than attempting to infer specific food content and portion size.…”
Section: Sensing Food Practicementioning
confidence: 99%
“…The city is home to several universities. Together with our local collaborators, we recruited students from two universities [46]. The recruitment campaign was launched in June 2019.…”
Section: Exploratory Data Collectionmentioning
confidence: 99%
“…Results from the initial data analysis showed that smartphone sensing can be used to infer self-perceived levels of eating behavior with an accuracy of 87% in a three-class inference task [46]. In addition, sensing can be used to analyze the social contexts in which students eat during the day, and infer a basic classification of social eating (eating alone or with others) with an accuracy of 84% [45].…”
Section: Exploratory Data Collectionmentioning
confidence: 99%
“…Smartphones allow sensing health and well-being aspects via continuous and interaction sensing techniques, both of which are generally called passive sensing [71]. This capability has been used in areas such as stress [13,67], mood [62,102], depression [14,112], well-being [57,63], and eating behavior [12,72,74]. If we consider drinking related research in mobile sensing, Bae et al [6] conducted an experiment with 30 young adults for 28 days, and used smartphone sensor data to infer non-drinking, drinking, and heavy-drinking episodes with an accuracy of 96.6%.…”
Section: Smartphonementioning
confidence: 99%
“…Even though gaining a holistic understanding regarding eating or drinking behavior is impossible without capturing contextual aspects regarding such behaviors, prior work has shown that people tend to reduce the usage of apps that require a large number of self-reports, and tend to use health and well-being applications that function passively [71]. Mobile sensing offers the opportunity to infer attributes that otherwise require user self-reports, hence reducing user burden [71,72,74]. In addition, mobile sensing could infer attributes to facilitate search acceleration in food/drink logging apps [39].…”
Section: Introductionmentioning
confidence: 99%